Daptomycin-induced acute eosinophilic pneumonia: Analysis of the current data and illustrative case reports. (October 2013) - Phillips, Jason; Cardile, Anthony P.; Patterson, Thomas F.; Lewis, James S.
Abstract Acute eosinophilic pneumonia (AEP) is a rare but important complication of daptomycin therapy. We describe 2 cases of daptomycin-associated AEP, compile available data from another 22 published cases, and propose a revised set of diagnostic criteria.